BL_GERICHTE 715 2011 445 / 231 vom 17. Mai 2011 , Entscheid des Kantonsgerichts Basel-Landschaft, Abteilung Sozialversicherungsrecht vom 16. August 2012 (715 11 445 / 231) - BL Gerichte (2011)
Insolvenzentschädigung